Do cabimento de recurso extraordinário ante a homologação de sentença estrangeira - Machado, Maria Olívia Rodrigues (2007)
The international legal cooperation represents an important way to improve the relationship among nations. Due to the globalization evolution, the barriers among countries have been decreasing considerably, leading to a bigger circulation of goods, people and capital. The development of new methods help improve the relationship among nations, as well as the improvement of the international legal cooperation, thus, creating a larger respect and coordination among countries that are seeking validity/accomplishment of their decisions in other States. The reciprocity of having alien decisions being accomplished in each others territory, in other words, a policy of reciprocity assistance between sovereign entities. In Brazil, there was an important change brought by the edition of the Constitutional Amendment nº 45 on December 30th, 2004. This legislative instrument transferred the original competence to decide about the exequatur of a letter rogatory and to homologate foreign sentences to Superior Tribunal de Justiça. The present study aims to show the pertinence about the possibility of the Extraordinary Appeals to refute the decisions pronounced by STJ related to the approval of a foreign sentence, including also the newest of them, the general repercussion The objective is to make a perfected and meticulous study to conclude in a coherent and justified way about the viability or not of this instrument of impugnation